Waste Bank Management In Waste Processing At Environmental Health Diploma Program In Magetan Campus - Frida Hendra Rinata; Tuhu Pinardi (Humanistic Network for Science and Technology (HNST), 2019)
Waste problem in Magetan is harder problem. The waste occurrence rate that enters to the waste landfill site reaches ±149.15 m3/ day. Therefore, it is needed to build new management innovations to manage waste in schools and campuses.Moreover, this study aimed to describe management concept of the